The Novel “Amata”: An Analysis of Immortality According to the Principles of The Three Characteristics in Buddhism and Scientific - Suwannamas, Dechawat; Meekhum, Maneenuch; Promsa, Apinya; Naijarun, Khwanchanok (Trends of Humanities and Social Sciences Research, 2020)
This research had as objectives to: 1) study the relationship between immortality from the perspective of Buddhism and science, 2) to study the differences between immortality from the perspective of Buddhism and science from the novel about “Amata” of Wimon Saininuan. This study was a qualitative research. Data were analyzed using descriptive analysis. The research results found that immortality from the Buddhism and science perspective has a relationship as follows: Tilakkhana (the three characteristics) from the Aniccata (impermanence) in Buddhism and cloning from the science perspective see physical deterioration in the human body. Dukkhata (state of suffering) in Buddhism and cloning from the science perspective say that the physical deterioration in the human body with time makes humans uncomfortable, Stress and Conflict. Anatta (soullessness) perspective in Buddhism and cloning from the science perspective, tries to search for ways and solutions to create comfort and make the human being not sad and not distressed. The Novel concentrates on the human body. Therefore, Tilakkhana following the Buddhism perspective and Cloning from the science perspective has a relationship as all of them are concern about the existence of the body to make humans immortal, but they differ in their processes and practice. Buddhism teaches humans to accept things the way they happen in order enter nirvana (Niphphan) but the scientist think that humans can overcome the physical deteriorations in the human body. Therefore, they search and invent cloning to meet human needs make humans immortal.